Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1093/brain/awg040
|View full text |Cite
|
Sign up to set email alerts
|

Markers of endothelial dysfunction in lacunar infarction and ischaemic leukoaraiosis

Abstract: Patients with cerebral small vessel disease (SVD) can present as isolated lacunar infarction or with diffuse white matter changes, with the imaging appearance of leukoaraiosis. Endothelial dysfunction, which can lead to breakdown of the blood-brain barrier, impaired cerebral autoregulation and prothrombotic changes, is believed to be important in mediating disease. Circulating levels of intercellular adhesion molecule 1 (ICAM1), thrombomodulin (TM), tissue factor (TF) and tissue factor pathway inhibitor (TFPI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
323
3
10

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(345 citation statements)
references
References 48 publications
9
323
3
10
Order By: Relevance
“…One study of 116 patients found CRP to be significantly higher in patients with large vessel compared to small vessel ischemic strokes [43]. Lacunar stroke has also been shown to have higher levels of thrombomodulin, ICAM-1, tissue factor, and homocysteine compare to controls, though it is unclear whether this is different compared to other stroke subtypes [44,45]. Progression of white matter hyperintensities on MRI which may reflect small vessel disease has been associated with a higher plasma level of intercellular adhesion molecule (ICAM) [46].…”
Section: Biomarkers Of Ischemic Stroke Etiologymentioning
confidence: 99%
“…One study of 116 patients found CRP to be significantly higher in patients with large vessel compared to small vessel ischemic strokes [43]. Lacunar stroke has also been shown to have higher levels of thrombomodulin, ICAM-1, tissue factor, and homocysteine compare to controls, though it is unclear whether this is different compared to other stroke subtypes [44,45]. Progression of white matter hyperintensities on MRI which may reflect small vessel disease has been associated with a higher plasma level of intercellular adhesion molecule (ICAM) [46].…”
Section: Biomarkers Of Ischemic Stroke Etiologymentioning
confidence: 99%
“…15 In turn, endothelial abnormalities have recently been linked to cerebrovascular disease and reduced cognitive function. 9,16,17 Further research is needed to clarify the relation between BNP and these possible mechanisms.There are several limitations of the present study. Although BNP levels were significantly related to cognitive performance in the current sample, further examination in larger and more diverse samples would strengthen the generalizability of the findings.…”
mentioning
confidence: 99%
“…15 In turn, endothelial abnormalities have recently been linked to cerebrovascular disease and reduced cognitive function. 9,16,17 Further research is needed to clarify the relation between BNP and these possible mechanisms.…”
mentioning
confidence: 99%
“…As arterial narrowing increases, it leads to a decline in the perfusion of the capillary bed, which can result in discrete regions of lacunar infarction and/or more diffuse ischaemic changes in the periventricular and deep white matter called leukoaraiosis. 13 Chronic hypertension also predisposes to impaired blood brain barrier function, with endothelial cell retraction, increased vascular permeability and greater susceptibility to white matter injury for relatively small insults. The potential for white matter injury is further increased by the blood supply to the periventricular and deep white matter being dependent on end-arteries lacking appropriate anastamoses, thus creating an arterial watershed zone.…”
mentioning
confidence: 99%
“…11,13 Second only to age, hypertension has been shown to the most important risk factor for small vessel disease [3][4][5][6] and a complex and dynamic relationship between BP and cerebral function is being revealed; high BP may initially accelerate arteriosclerotic change and impair cerebral autoregulation with adverse effects on cognition but high BP may be required for adequate perfusion when arteries are diseased and cerebral autoregulation is impaired. Uncertainty surrounds the appropriate level of BP for optimum cognitive performance and the desirability of lowering of BP beyond a certain level in patients with established cerebral small vessel disease continues to be a subject of much debate.…”
mentioning
confidence: 99%